Anti-malarial Drugs as Potential Inhibitors of Leishmania Glycolytic Enzymes: Development of New Anti-leishmanial Agents - Bashir A. Yousef; Tanzeel H. Elwaseela; Tagwa A. Ali; Fatima E. Mohammed; Wala O. Mohammed; Majdi Alobaid; Amina I. Dirar (Universitas Padjadjaran, Indonesia, 2020)
Leishmaniasis is one of the most important endemic diseases in Sudan. The glycolytic pathway is one of the essential pathways in the survival and pathogenicity of the leishmania parasite. This study aimed to evaluate the antileishmanial activities of three antimalarial drugs through targeting the glycolytic pathway of the parasite. Anti-leishmanial activities of artesunate, quinine and mefloquine were evaluated using an in vitro anti-promastigote assay. Then, in silico molecular docking was conducted using Autodock 4.0 software to study the molecular interactions of antimalarial drugs to different key glycolytic enzymes. The results of the current study, Artesunate, quinine, and mefloquine showed effective inhibitory activities against L. donovani with IC50 values of 58.85, 40.24, and 20.06 μg/ml, respectively. Molecular docking analysis revealed interesting interactions between different antimalarial drugs and various glycolytic enzymes (Glucose-6-phosphate isomerase, Triosephosphate isomerase, Glycerol-3-phosphate dehydrogenase, Glyceraldehyde-3-phosphate dehydrogenase and Pyruvate kinase). Moreover, these drugs interact with different amino acid residues of the proteins with satisfactory binding energies, particularly with artesunate. According to binding energies, Glycerol-3-phosphate dehydrogenase was represented the most potential target for three tested drugs. Collectively, our results showed promising antileishmanial activities of different antimalarial that may mediated through inhibition of glycolysis process in leishmania donovani promastigote.